Modeling of liquid propellant combustion chamber - Pandit, Ajinkya V.; Kumar, Ashok; Rao, G. Srinivasa; Kedarnath, C.; Srihari, R.; Ranade, Vivek V. (Chemical Engineering Journal, 2012)
Liquid propellants are fuels which do not require external supply of oxygen for combustion. These fuels are widely used for propulsion applications in oxygen rare environments (underwater, space). We had previously presented a model for solid propellant decomposition in a combustion chamber. In this study we extend the model for the case of combined solid and liquid propellant combustion. Sub-models relating to solid propellant combustion and outlet flow-rate in the present study are borrowed from the previous study. The combustion chamber is assumed to be a `well-mixed reactor'. A model is developed to characterize the liquid propellant spray assuming the spray is a collection of individually burning droplets. A single droplet decomposition model was developed and used along-with the spray model to solve for the liquid propellant burning rate. Appropriate numerical methods and computer programs were developed to solve the model equations. The model predictions were compared with the experimental data obtained in earlier studies. Appropriate methodology for calibrating the model parameters was developed and its usefulness was demonstrated by comparing the simulated pressure profiles with the experimental pressure profiles. The presented model and results will be useful for selecting appropriate liquid propellants for propulsion systems and for the development of a system level model of propulsion systems. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Liquid propellant; Single droplet decomposition; Spray combustion

Bilayer cryogel wound dressing and skin regeneration grafts for the treatment of acute skinwounds - Priya, S. Geetha; Gupta, Ankur; Jain, Era; Sarkar, Joyita; Damania, Apeksha; Jagdale, Pankaj R.; Chaudhari, Bhushan P.; Gupta, Kailash C.; Kumar, Ashok (ACS Applied Materials & Interfaces, 2016)
In this study, the potential of cryogel bilayer wound dressing and skin regenerating graft for the treatment of surgically created full thickness wounds was evaluated. The top layer was composed of polyvinylpyrrolidone-iodine (PVP-I) and served as the antiseptic layer, while the bottom regenerative layer was made using gelatin cryogel. Both components of the bilayer showed typical features of a cryogel interconnected macropore network, rapid swelling, high water uptake capacity of about 90%. Both PVP and gelatin cryogel showed high tensile strength of 45 and 10 kPa, respectively. Gelatin cryogel sheets were essentially elastic and could be stretched without any visible deformation. The antiseptic PVP-I layer cryogel sheet showed sustained iodine release and suppressed microbial growth when tested with skin pathogens (zone of inhibition cm for sheet of 0.9 cm diameter). The gelatin cryogel sheet degraded in vitro in weeks. The gelatin cryogel sheet supported cell infiltration, attachment, and proliferation of fibroblasts and keratinocytes. Microparticles loaded with bioactive molecules (mannose-6-phosphate and human fibrinogen) were also incorporated in the gelatin cryogel sheets for their role in enhancing skin regeneration and scar free wound healing. In vivo evaluation of healing capacity of the bilayer cryogel was checked in rabbits by creating full thickness wound, defect (diameter 2 cm). Macroscopic and microscopic observation at regular time intervals for 4 weeks demonstrated better and faster skin regeneration in the wound treated with cryogel bilayer as compared to untreated defect and the repair was comparable to commercial skin regeneration scaffold Neuskin-F. Complete skin regeneration was observed after 4 weeks' of implantation with no sign of inflammatory response. Defects implanted with cryogel having mannose-6-phosphate showed no scar formation,, while the wound treated with bilayer incorporated with human fibrinogen microparticles showed early signs of skin regeneration; epidermis formation occurred at 2 weeks after implantation.

Photogating induced high sensitivity and speed from heterostructure of few-layer MoS2 and reduced graphene oxide-based photodetector - Das, Chayan; Kumar, Ashok; Kumar, Suresh; Dambhare, Neha V.; Kumar, Mahesh; Rath, Arup K.; Sahu, Satyajit (Physical Chemistry Chemical Physics, 2023)
Over the past few years, two-dimensional transition metal dichalcogenides (2D-TMDC) have attracted huge attention due to their high mobility, high absorbance, and high performance in generating excitons (electron and hole pairs). Especially, 2D molybdenum disulfide (MoS2) has been extensively used in optoelectronic and photovoltaic applications. Due to the low photo-to-dark current ratio (I-photo/dark) and low speed, pristine MoS2-based devices are unsuitable for these applications. So, they need some improvements, i.e., by adding layers or decorating with materials of complementary majority charges. In this work, we decorated pristine MoS2 with reduced graphene oxide (rGO) and got improved dark current, I-photo/dark, and response time. When we compared the performance of pristine MoS2 based device and rGO decorated MoS2 based device, the rGO/MoS2-based device showed an improved performance of responsivity of 3.36 A W-1, along with an I-photo/dark of about 154. The heterojunction device exhibited a detectivity of 4.75 x 10(12) Jones, along with a very low response time of 0.184 ms. The stability is also outstanding having the same device performance even after six months.